Petroleum Hydrocarbons Contamination Profile of Ochani Stream in Ejamah Ebubu, Eleme Local Government Area of Rivers State, Nigeria - Akuro Adoki (Journal of Applied Sciences and Environmental Management)
Petroleum hydrocarbon contamination profile, heavy metals and some physicochemical parameters were investigated in Ochani Stream site in Ejamah Ebubu, Eleme Local Government Area of Rivers State. The results show that a major crude oil spillage occurred at Ejamah Ebubu, Rivers State, Nigeria approximately 30 years ago. This assessment of study of the status of the site within the immediate vicinity of the spill revealed the existence of the Ochani Stream site further downstream. With this study, the state of the hydrocarbon contamination resulting from the spill has been identified. The nature and extent of the petroleum hydrocarbon contamination across the Ochani Stream site has been defined. The study revealed a total number of nine dump pits on this site. The pits contained weathered crude oil. Seven of them were located on the elevated dry land to the southwest and slope towards the swampy bush. The other two were located on the opposite side of the stream, to the north of the swamps. The pits which had an average depth of 1.14m, representing a total surface area of about 184m2 and a total volume of the order of 220m3 of heavily contaminated sludge. The contamination within the swampy area was non-homogenous and randomly distributed. Total Petroleum Hydrocarbon contamination levels varied widely across the site, from negligible, to heavily contaminated. Depth of contamination was very shallow. At an estimated average depth of 150mm over an area of 6.05 Ha the total volume of contaminated soil/sediment was 9075m3. The levels of toxic species such as heavy metals, PAH and BTEX compounds were found to be very low and they do not pose a significant environmental hazard. @JASEM